A posse para fins de moradia nas áreas urbanas - Ananias, Vanessa Drumond Patrus (2014)
This dissertation has as its central theme the possession that begins with the main intention of establishment of housing in urban areas. This research has focused the legislative treatment to the right to housing receives in the brazilian legal system, constitutional and infra-constitutional. The right to housing was established in article 6° of the Constitution of the Republic of 1988 as a social right and it is also integrates individual rights and guarantees. The housing is prominent institute in brazilian Magna Carta, in the Civil Code and in the statute of the city. This applies in the cases of adverse possession with tight deadlines, in the collective occupations and in the concession of special use. In all these legal predictions the purpose of housing is constitutive element of norm and confers differentiated possession discipline phenomenon and its legal consequences. The housing connects to the principle and foundation of human person dignity, so that in many situations the housing shortage hampers or prevents the achievement of that principle. The occupations that are focus in housing, confers to the social function of property special understanding, once that accentuates the need for exercise proprietary faculties inserted in the community